A google earth engine approach for anthropogenic forest fire assessment with remote sensing data in Rema-Kalenga wildlife sanctuary, Bangladesh - Mohammed; Ariful Khan; Angana Kuri; Sohag Ahammed; Kazi Al Muqtadir Abir; Mohammed A.S. Arfin-Khan (Geology, Ecology, and Landscapes)
Due to global climate change, fire dynamics around the world are changing around the world affecting regions more severely that had negligible exposure to forest fire. In this study, we assessed the effect of anthropogenic forest fire using the Normalized Burn Ratio in Rema-Kalenga Wildlife Sanctuary, Bangladesh while evaluating the relationship of this fire index with different spectral indices, and Soil and Vegetation properties. A Correlation and a regression analysis were used to examine the association of different variables with fire severity and One-way analysis of variances (ANOVA) test was also performed to inspect the damage done by fire and the regrowth potential of the forest ecosystem. According to the result, the total burned area was not alarming. Also, the relationship of fire index with spectral indices, and soil and vegetation properties have been meaningful to understand the impact of the forest fire in Rema-Kalenga. Additionally, significant effects of the fire on the variation of the different properties were also observed. Even though the quantity of burned area in this forest was not significant, fire management in the forest conservation strategies in Bangladesh should be heeded and incorporated to avoid future disasters, keeping in mind the future climate change.